Communication System Between Electric Vehicle and Electric Vehicle Charging Station Based on AC Powerline Carrier - Gustyan Sukmara, Reza; Purnama, Irwan; Rusdinar , Angga (eProceedings of Engineering, 2025)
Abstract - Electric vehicles are increasingly common in everyday life, especially in developed countries, while Indonesia is starting to adopt this concept. In electric vehicles, the Controller Area Network (CAN) serves as a central hub for data distribution throughout the vehicle, managing information from sensors, component status, and more. Charging is an important aspect of electric vehicles, which is crucial for the proper functioning of the vehicle. Establishing a communication link between the vehicle and the charging station offers significant benefits to both the user and the vehicle, enabling real-time diagnostics during routine charging. This is the driving force behind the development of Electric Vehicle Power Line Communication (EVPLC). The purpose of EVPLC is to enable data transfer through a two-way communication system via AC current used to charge the vehicle's battery. Researchers have developed an EVPLC module and validated the concept through simulations of an Electric Vehicle Charging Station (EVCS) and Electric Vehicle Controller Area Network (EVCAN). This approach aims to demonstrate the feasibility of implementing EVPLC in real-world charging stations and electric vehicles, ensuring efficient communication and diagnostics during the charging process. Keywords - CAN, Bidirectional, EVCS, EVCAN, AC, electric vehicle.